Verification of an emerging LCA design tool through real life performance monitoring - Eon, Christine; Murphy, L.; Byrne, Joshua; Anda, M. (2017)
Recent research has demonstrated that low-emission houses often underperform, consuming more energy than predicted by their designs. Life cycle assessments (LCA) have been employed to complement mandatory energy assessments, as they offer a more comprehensive evaluation of greenhouse gas (GHG) emissions over the building lifespan. This research monitored ten energy efficient Australian houses and recorded data about energy use and photovoltaic generation over 1 year. The houses were assessed with a relatively new LCA tool in addition to the Australian mandatory house energy assessment Nationwide House Energy Rating Scheme (NatHERS). The objective of this study was twofold: first, to evaluate the results of the assessment tools compared to actual house energy requirements and second, to understand how design, renewable energy, and occupancy can impact the overall GHG emissions of the houses. The results show that energy use is positively related to NatHERS ratings, but some of the high performance houses perform poorly and there was significant variation in energy use between houses with the same ratings. The LCA revealed that modern houses have higher embodied energy than older houses, while solar panels are not always used to their full potential. This paper attributes some of the variations between theoretical and actual energy use to construction issues and occupant practices.